Backpack Snow Shovel/Snow Kit and Ahkio Snow Shovel/Snow Saw Kit - Carney, Joseph L. (1974)
Two snow shovel kits were developed for use in an arctic environment. One shovel having a detachable handle and a nylon cloth carrying container is for backpacking by the individual soldier. A larger, more durable shovel is for use in conjunction with the man-hauled sled (Ahkio). A snow saw in a scabbard is provided which can be attached either to the handle of the Ahkio shovel, to the disassembled backpack shovel in the carrying case, to the rucksack or to the belt.